Article RETRACTED due to manipulation by the authors Primary physical education teachers as ethical and moral agents of the alpha generation students - Mashuri Eko Winarno; Amung Ma'mun; Eko Purnomo; Imam Hariadi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Ethics is a set of rules and principles in human life, and schools are at the forefront of developing moral education through physical education subjects. The purpose of this study is to investigate the role of physical education teachers in instilling attitudes of universal values in sports. The method used was descriptive. Data collection was conducted through forum group discussions and the distribution of a questionnaire consisting of 18 questions. The participants in this study were 72 physical education teachers in elementary schools spread across the Malang-raya area. This study produces a description and description of the role of teachers in emphasizing ethical and moral attitudes including, respect for the rules, respect for others, fairplay, self-esteem, honesty, tolerance.